2021
DOI: 10.3390/app11125506
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impacts of Climate Change on Shrimps Distribution of Commercial Importance in the Gulf of California

Abstract: The Gulf of California is the most productive fishing region in Mexico; its ecosystems contain a vast diversity of species with exploitation potential, some of them potentially vulnerable to climate change. This research was conducted to analyze, through habitat suitability models, the possible alterations in the distribution of the three shrimp species of the most importance for commercial fishing in the region: Litopenaeus stylirostris, Litopenaeus vannamei, and Farfantepenaeus californiensis. Habitat suitab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…According to our SDM results, the crucial factors influencing the spatiotemporal distribution of the shallower water shrimps L. occidentalis and X. riveti are bottom temperature and salinity. This finding aligns with research conducted on other shallow shrimp species in diverse regions, such as Mexico (Cota-Durán et al, 2021), Brazil (Lopes et al, 2017), the Persian Gulf, the coasts of North, East, and West Australia, and the North of the Arabian Sea (Sharifian et al, 2022;Sharifian et al, 2023). However, in these studies, bathymetry consistently emerged as a significant variable shaping shrimp habitat suitability alongside temperature.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…According to our SDM results, the crucial factors influencing the spatiotemporal distribution of the shallower water shrimps L. occidentalis and X. riveti are bottom temperature and salinity. This finding aligns with research conducted on other shallow shrimp species in diverse regions, such as Mexico (Cota-Durán et al, 2021), Brazil (Lopes et al, 2017), the Persian Gulf, the coasts of North, East, and West Australia, and the North of the Arabian Sea (Sharifian et al, 2022;Sharifian et al, 2023). However, in these studies, bathymetry consistently emerged as a significant variable shaping shrimp habitat suitability alongside temperature.…”
Section: Discussionsupporting
confidence: 86%
“…Such alterations, compounded by overfishing, lead to shifts in species composition and distribution, with potential consequences for the productivity of shrimp fisheries (Sharifian et al 2023). As the global temperature rise accelerates, these changes underscore the criticality of understanding and mitigating the effects on shrimp populations (Basher et al 2016;Cota-Durán et al 2021). As of now, only a limited number of climate change simulations have been conducted for shrimp species distributions.…”
Section: Introductionmentioning
confidence: 99%
“…One of the characteristics of short-lived populations is their dependence on the environment. In the case of penaeid shrimp, this feature has been widely reported in the literature (Garcia, 1988;Garcia, 1996;Arreguin-Sanchez et al, 2015;Diop et al, 2015;Lopes et al, 2018), including climate variability and its effects on blue shrimp populations the Gulf of California (Galindo-Bect et al, 2000;Castro-Ortiz and Lluch-Belda, 2008;Perez-Arvizu et al, 2009;Santamaria-del-Angel et al, 2011;Paéz-Osuna et al, 2016;Cota-Durań et al, 2021). In the case study, given the evidence reported in the literature, a brief analysis of the contribution of environmental variability in the context of the Kobe diagram, particularly related to PRR Lim , is provided.…”
Section: Considerations Of Environmental Effectsmentioning
confidence: 81%